Parental Involvement on Home Schooling of Basic Level Children in Nepal - Basnyat, Samjhana (Educational Journal, 2023)
This article explores the Parental Involvement on Home Schooling Practice of Basic Level children during and after COVID in Nepal. Many nations put emergency preparations into action because of COVID-19, including lockdowns and closing of schools. Families are now needed to support their children's learning at home due to the new circumstances that have greatly impacted them. COVID pandemic forced students' schools to close, schools are requiring hybrid homeschooling methods. Analyzing parents' impressions of them at-home involvement in their kids' education was the goal of the current study. For the characteristics of home learning, parental involvement, and pupils' learning activities, a basic qualitative method based on interviews and a small number of observations was used. Nine parents with kids in elementary school were used as a sample group for the data collection. Findings showed that parents helped their children during the epidemic by primarily keeping an eye on their focus in class and helping those complete tasks. However, a number of factors seem to play a substantial role in determining parental engagement time, effort, motivation, support for instruction, and learning environment creation. The results also show that parents especially of elementary school children must commit a large amount of time in preparing them for home school activities. The discussion of the implications for policies, schools, and families aims to support children's learning and the success of homeschooling.